2015
DOI: 10.1002/jor.23074
|View full text |Cite
|
Sign up to set email alerts
|

FE analysis of the effects of simplifications in experimental testing on micromotions of uncemented femoral knee implants

Abstract: Experimental testing of orthopaedic implants requires simplifications concerning load application and activities being analyzed. This computational study investigated how these simplifications affect micromotions at the bone-implant interface of an uncemented femoral knee implant. As a basis, validated in vivo loads of the stance phase of gait and a deep knee bend were adopted. Eventually, three configurations were considered: (i) simulation of the complete loading cycle; (ii) inclusion of only tibiofemoral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
(53 reference statements)
3
10
0
Order By: Relevance
“…In Berahmani et al, the M‐L distribution was kept constant for both simplified and full loading conditions; whereas, in the present study the M‐L distribution of the tibiofemoral force was 51–49% while replicating the in vitro conditions and 60–40% under physiological loading conditions. This along with other factors, such as implant geometry and modelling parameters selected (e.g., frictional coefficients, and applied loads) may also explain why, contrary to that reported by Berhamani et al the distal surface and anterior chamfers were found to exhibit high levels of micromotion under complex loading conditions.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In Berahmani et al, the M‐L distribution was kept constant for both simplified and full loading conditions; whereas, in the present study the M‐L distribution of the tibiofemoral force was 51–49% while replicating the in vitro conditions and 60–40% under physiological loading conditions. This along with other factors, such as implant geometry and modelling parameters selected (e.g., frictional coefficients, and applied loads) may also explain why, contrary to that reported by Berhamani et al the distal surface and anterior chamfers were found to exhibit high levels of micromotion under complex loading conditions.…”
Section: Discussionmentioning
confidence: 74%
“…In a recent FE study by Berahmani et al, the influence of different loading configurations on micromotion at the bone–implant interface following primary TKA with a cruciate retaining implant was examined. Similar to the finding of the present study, Berahmani et al reported that simplified loading conditions and a lack of patella–femoral force caused an overestimation of micromotion at the interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that surrogate models have significant potential to rapidly predict micromotion over the entire bone-implant interface, allowing greater range in loading conditions to be explored than is possible through conventional methods. Berahmani et al also studied how these simplifications affect micromotions at the bone-implant interface of an uncemented femoral component (Berahmani et al, 2016). They suggested that a simplified peak force can be used to assess the stability of cementless femoral components.…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%